How hard did you try? A scoping review of the literature on effort investment in math - Nguyen, Nghi; Suárez-Pellicioni, Macarena (Frontiers in Education, 2025)
Like most high-level human skills, such as reading or playing the piano, learning math requires thousands of hours of effort. Despite its importance, research on effort in math remains limited. This scoping review examines the literature on effort in math, focusing on individual variables (i.e., sex, age, skills, attitudes) and contextual factors (i.e., teacher involvement, parental support, SES, cultural differences) that influence effort investment in math. It explores how effort contributes to math achievement, predicts gains over time, and mediates the effects of affective factors, showing how positive attitudes enhance performance through increased effort and how lack of effort mediates the negative impact of math anxiety. The review highlights the foundational role of effort in fostering positive attitudes and emotions in math and offers strategies to motivate students to invest effort in math learning.